Absorption kinetics of CO2 in novel formulated 2-amino-2-methyl-1-propanol and N-methyl-4-piperidinol solvent. (November 2020) - Sema, Teerawat; Ranong, Pipat Na; Kiattinirachara, Thanthip; Posoknistakul, Pattaraporn; Jiraratananon, Ratana; Tontiwachwuthikul, Paitoon
Abstract: In the present study, kinetics of CO2 absorption in novel formulated 2-amino-2-methyl-1-propanol (AMP) and N-methyl-4-piperidinol (MPDL) solvent was investigated in a stirred tank reactor over ranges of temperature (303–333 K) and concentration (5% wt. AMP-25% wt. MPDL, 10% wt. AMP-20% wt. MPDL, and 15% wt. AMP-15% wt. MPDL). A drop of pressure method was used to determine the kinetics of CO2 absorption in terms of overall reaction kinetics constant ( k ov ) through a slope of the drop of pressure plot. It was found that the k ov increased as temperature increased and increased as concentration of AMP in AMP-MPDL solvent increased over ranges of studied temperature and concentration. The results also showed that 15% wt. AMP-15% wt. MPDL possessed the highest CO2 absorption kinetics among the three concentrations. More importantly, the novel formulated 15% wt. AMP-15% wt. MPDL solvent was found to have considerable faster CO2 absorption than the conventional 15% wt. AMP-15% wt. triethanolamine (TEA) and 30% wt. TEA solvents, respectively. Based on these observations, it can be summarized that an addition of AMP into MPDL solvent can enhance the overall CO2 absorption performance of the formulated AMP-MPDL solvent. Additionally, it can be suggested that the novel formulated AMP-MPDL has a great potential to be used as an alternative solvent for capturing CO2 in terms of reaction kinetics; especially, in substitution of conventional AMP-TEA and TEA solvents.